Microstructure Design and Performance Optimization of Constant Modulus Pentamode Materials Acoustic Cloak - Ziyin Luo; Qizheng Zhou; Peng Guo (Crystals, 2022)
Underwater acoustic stealth has great scientific research value. According to acoustic coordinate transformation theory, the acoustic stealth cloak based on pentamode materials can realize underwater broadband acoustic stealth. However, due to the correlation between the density and modulus of pentamode materials and the changes in the parameters of each layer of the acoustic stealth cloak, a large amount of structural optimization work is required for the pentamode material to meet the specific parameter requirements, which significantly increases the difficulty of the pentamode acoustic stealth cloak design. To simplify the design process, inspired by the calculation of equivalent modulus by representation volume element, this article proposed a pentamode material configuration with independent variation of density and modulus and designed a 1 m radius acoustic stealth cloak with a specific structure of pentamode materials matching the coordinate transformation equation of constant modal mapping. After simulation calculation and optimization design, in the range of <semantics>a/λ</semantics> from 0 to 1, the average total scattering cross-section of the cavity with a radius of 0.5 m covered by the acoustic stealth cloak is 0.858; the average total scattering cross-section of the cavity is 19.718 after removing the pentamode material acoustic stealth cloak. The results of the study are expected to provide some method references for simplifying the design process of the pentamode material acoustic stealth cloak and the microstructure design of the pentamode materials.